Case report: Alpelisib-induced Stevens–Johnson syndrome - Kurian, Christine Jane; Desai, Akshay; Rafferty, William; Abou Hussein, Ahmed Kamel (Frontiers in Oncology, 2022)
Background Alpelisib is a recently approved treatment for hormone receptor-positive, HER2-negative, PIK3CA-mutated advanced breast cancer. It has been associated with alopecia and rash, but there are no documented cases of Stevens–Johnson Syndrome (SJS) associated with this drug. Here, we detail the first case of SJS associated with alpelisib. Case description Our patient is a 60-year-old woman with a past medical history of metastatic hormone receptor-positive (ER+ 80% and PR+ 1%), HER2-negative metastatic breast cancer who presented with acute odynophagia, fevers, and diffuse body rash after receiving her first doses of alpelisib and fulvestrant in the preceding days. She presented to the emergency department after developing a whole-body rash and severe ulceration of her buccal mucosa. She was started on methylprednisolone with remarkable improvement in symptoms. Conclusion This case report details the only report of SJS following alpelisib treatment. Immediate cessation of drugs and initiation of steroids are the cornerstone of treatment. Patients who experience such side effects will have to be monitored closely for long-term sequelae associated with SJS, including cutaneous, ocular, and oral sequelae, all of which can profoundly affect the quality of life for cancer patients.